Krause's food & the nutrition care process
The most respected nutrition text for more than 50 years, Krause's Food and the Nutrition Care Process delivers comprehensive and up-to-date information from respected educators and practitioners in the field. The latest recommendations include the new MyPlate guide, the Dietary Guidelines for Americans 2010, new and expanded chapters, and a large variety of tables, boxes, and pathophysiology algorithms, all providing need-to-know information with ease. New co-editor Janice L. Raymond joins L. Kathleen Mahan and Sylvia Escott-Stump and nearly 50 leading educators, researchers, and practitioners in writing a nutrition text that's ideal for use in class or everyday practice